Transformation of Higher Education Institutions in Malaysia: A Review - Sara Asmawati, Shariffuddin; Jamal Rizal, Razali; Mislaiha, A. Ghani; Wan Raihan, Wan Shaaidi; Ismi Safia Adilah, Ibrahim (Global Business and Social Entrepreneurship Resources, 2017)
Transformation of higher education has affected tertiary institutions in every part of the globe. Even though, the key factors are generally common around the world, the types of higher education institutions transformation and issues emerge in the change process may vary from one country to another. This paper reviews and discusses about recent studies on the transformation involving different types of higher education institutions that have significantly occurred in Malaysia. Pertinent studies between 2010 until 2015 were researched and selected using multiple online database and direct search engine. The results indicated that four types of Malaysian higher education institution transformation were identified in these studies. Apart from that, the key elements prevalent in the transformation process were also identified and categorized. These findings are significant as they show that more researches on the transformation of other types of higher education institutions in Malaysian context should be conducted. This is due to the fact that, the transformation of the higher education institution impinges on the stakeholders, such as the policymakers, administrators,academics, students, parents, study loan/scholarship providers to mention a few in many different aspects